Oral contraceptive cycle phase does not affect 200-m swim time trial performance - Rechichi, C.; Dawson, B. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to examine whether swimming performance was affected by acute hormonal fluctuation within a monophasic oral contraceptive (OC) cycle. Six competitive swimmers and water polo players completed a 200-m time trial at 3 time points of a single OC cycle: during the consumption phase (CONS), early (WITH1), and late in the withdrawal phase (WITH2). Split times and stroke rate were recorded during the time trial, and heart rate, blood lactate, glucose, and pH were measured after each performance test. Resting endogenous serum estradiol and progesterone concentrations were also assessed. No significant differences were observed between phases for body composition, 200-m swim time, mean stroke rate, peak heart rate, or blood glucose (p > 0.05). The mean peak blood lactate was significantly lower during WITH2 (9.9 ± 3.0 mmol/L) compared with that of CONS (12.5 ± 3.0 mmol/L) and mean pH higher during WITH2 (7.183 ± 0.111) compared with that of CONS (7.144 ± 0.092). Serum estradiol levels were significantly greater during WITH2 compared with that during WITH1 and CONS, but there was no difference in serum progesterone levels. These results demonstrate that for monophasic OC users, cycle phase does not impact the 200-m swimming performance. There was a reduction in blood lactate and an increase in pH during the withdrawal phase, possibly because of an increase in fluid retention, plasma volume, and cellular alkalosis. Therefore, female 200-m swimmers taking a monophasic OC need not be concerned by the phase of their cycle with regard to competition and optimizing performance. However, coaches and scientists should exercise caution when interpreting blood lactate results obtained from swimming tests and consider controlling for cycle phase for athletes taking an OC.